Abnormal Brain MRI Findings in Anti-N-Methyl-D-Aspartate Receptor Encephalitis and Correlation With Outcomes - Lei, Chunyan; Chang, Xiaolong; Li, Haijiang; Zhong, Lianmei (Frontiers in Neurology, 2022)
Purpose The reported prevalence of abnormal findings by brain MRI varies from 11 to 83% among patients with anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis. Here, we investigated the prevalence of abnormal MRI findings in Chinese patients and explored whether such findings are correlated with clinical outcomes. Methods This retrospective study analyzed a consecutive series of 52 patients with anti-NMDAR encephalitis admitted to our hospital. The patients were assigned to the “MRI-normal” or the “MRI-abnormal” group based on brain MRI after admission. The groups were compared in terms of clinicodemographic characteristics and scores on the Mini-Mental State Examination (MMSE) and modified Rankin Scale (mRS) 3 and 12 months after admission. Results Thirty-seven (71.15%) of the patients showed abnormalities on brain MRI; these patients were more likely to be men and showed abnormalities on electroencephalography. Patients who showed normal or abnormal MRI findings did not differ significantly in terms of clinical symptoms, rates of mortality or relapse, or mRS scores after 3 and 12 months. However, patients with abnormal MRI showed significantly lower MMSE scores than those with normal MRI after 3 and 12 months. Conclusions We found high prevalence of abnormal MRI findings in our sample of Chinese patients with anti-NMDAR encephalitis. We also found that the abnormal findings were associated with cognitive decline but not necessarily with mortality or functional outcomes in the short or long term.